Evolutionary processes in the natural history of religion: body, brain, belief - Hemminger, Hansjörg (New approaches to the scientific study of religion, 2021)
Intro -- Introduction -- Contents -- Part I: Religion Through the Eyes of a Biologist -- Evolution in All Its Facets -- References -- The Scientific Approach to Religion -- References -- What Do We Know? What Can Be Known? -- References -- Understanding Religion from the Inside -- References -- Part II: About Evolutionary Biology and the Evolution of Religion -- Evolution: The Modern Synthesis -- References -- Extended Evolutionary Synthesis, Epigenetics and the Contingency of Evolution -- References -- Gene-Culture Coevolution -- References -- Part III: Phenomenology of Paleolithic Religion -- A Story Told Backwards -- References -- The Beginning and the End: Pre-Human and Neolithic Religion -- References -- Hominin Pre-Adaptations: Background to the Evolution of Religion -- References -- Part IV: CSR: The Cognitive Science of Religion -- Evolutionary Psychology and Religion -- References -- Religious Fanaticism -- References -- Practical Religion and Spirituality -- References -- Magic, Religion and Evolutionary Ethics -- References -- Part V: Modeling the Evolutionary Path to Culture and Religion -- Multi-Level Models of Religious Evolution -- References -- Conclusion and Outlook -- References.